Antibacterial effect of Raphanus sativus (Radish) root juice on growth performance and caecal bacterial load of broiler chickens - Adeleye, Oluwagbemiga Olanrewaju; Majekodunmi, Bukola Christiana; Abatan, Munirat Olaide; Obuotor, Tolulope Mobolaji; Kolawole, Amos Oyebisi Kolawole (Acta Scientiarum. Biological Sciences, 2024)
Majority of poultry producers have been concerned about the microbial colonization of chicken guts, which usually result in competition for nutrient and poor health. As a way to combat this, antibiotics are used, however, this has led to antibiotic resistance and the presence of antibiotic residues in poultry products. Therefore, the purpose of this study is to ascertain the effect of radish root juice on the microbiota in the caecum of broiler chickens while also monitoring their growth response. This study was a 2 by 3 factorial layout. There were six treatment groups of forty day-old broiler chicks each, consisting of two dosages of radish juice (10 mL L-1 or 15mL L-1 of the birds’ drinking water) and three frequencies of administration (0, 2 and 3 times weekly). The zero frequencies (no juice) were the control groups given Enrofloxacin as antibiotic (1 mL in 4 L of drinking). At the starter and finisher phase, birds were given commercial diets. The growth performance was evaluated at both phases, while the microbial load for each group was determined at the finisher phase. The contents of the birds’ caeca were taken for microbial analysis at 42nd day of the experiment. Frequency and nature of microorganism were obtained. Microbial count of broilers administered radish juice ranged from 7.84 x 107 – 1.75 x 107 cfu mL-1 while those administered antibiotics had 8.75 x 107 – 8.56 x107 cfu mL-1. Microorganisms isolated include: Klebsiella Pneumoniae (27%), Morganella morganii (24%), Bacillus subtilis (22%), Providencia rettgerii (5%), Staphylococcus saprophyticus (5%), Staphylococcus aureus (4%), Citrobacter fruendii (4%), Proteus mirabilis (2%), Micrococcus luteus (2%), Escherichia coli (2%), Providencia stuartii (2%). There was no statistical difference (P>0.05) among all the growth parameters in both the radish groups and the antibiotic groups, at the starter and finisher phase. This study suggests radish root juice as an effective antimicrobial agent in reducing microbial load of the gut of broilers which consequently can lead to increased productivity and feed – to – meat conversion ratio.